The rationalized form of the expression will be [tex]-1+\sqrt{2}}[/tex]
Given the rational function
[tex]\frac{\sqrt{12}}{\sqrt{3}-3}\\[/tex]
Multiplying by the conjugate of the denominator
[tex]=\frac{\sqrt{12}}{\sqrt{3}-3}\times \frac{\sqrt{3}+3}{\sqrt{3}+3}\\=\frac{\sqrt{12}(\sqrt{3}+3)}{3-9}\\ =\frac{(\sqrt{36}+3\sqrt{12})}{3-9}\\=\frac{6+6\sqrt{2}}{-6}\\ =[/tex]
Simplifying further will give:
[tex]-1+\sqrt{2}}[/tex]
Hence the rationalized form of the expression will be [tex]-1+\sqrt{2}}[/tex]
Learn more on rationalization here: https://brainly.com/question/14261303